Turn right at machu picchu eaudiobook Rediscovering the lost city one step at a time. - Adams, Mark (2012)
What happens when an unadventurous adventure writer tries to re-create the original expedition to Machu Picchu? In 1911, Hiram Bingham III climbed into the Andes Mountains of Peru and "discovered" Machu Picchu. While history has recast Bingham as a villain who stole both priceless artifacts and credit for finding the great archeological site, Mark Adams set out to retrace the explorer's perilous path in search of the truth-except he'd written about adventure far more than he'd actually lived it. In fact, he'd never even slept in a tent. Turn Right at Machu Picchu is Adams' fascinating and funny account of his journey through some of the world's most majestic, historic, and remote landscapes guided only by a hard-as-nails Australian survivalist and one nagging question: Just what was Machu Picchu?